Literature review of inorganic ultraviolet radiation filters - Stefanik, Lydia R. (Kansas State University, 2012)
The damage that can be inflicted by ultraviolet radiation has gained widespread interest. Traditionally sunscreens are made of organic and inorganic components that block two of the three types of ultraviolet radiation, UVA and UVB. This report is a literature review of several articles that have investigated the effects of inorganic UV filters; specifically titanium dioxide and cerium dioxide. There are concerns about absorption of titanium dioxide into the skin and the adverse reactions that could occur, but it was found that there is little to no absorption. Similarly the photostability of titanium dioxide is a concern; this was found to be remedied in part by a surface treatment to the titanium dioxide. The combination of titanium dioxide and carnauba wax was also studied and found to enhance the properties of both the organic and inorganic filters. Ceria was studied as a possible replacement for titanium dioxide. It was found to have similar ultraviolet shielding properties while minimizing the photocatalytic activity and photocytotoxicity seen in titanium dioxide.
Keywords: Sunscreen; Titanium Dioxide; Cerium Dioxide; Inorganic filters; Ultraviolet radiation; Chemical Engineering (0542); Toxicology (0383)